Pre-service Teachers’ Use and Usefulness of Blackboard Learning Management Systems for Self-Regulated Learning - Israel Kibirige; Ronald James Odora (Universitas Pendidikan Ganesha, 2023)
Although BLB has many applications students use, it is not clear which applications are used most and perceived most useful for Self-Regulated Learning (SRL). The objective of this research is to establish applications pre-service teachers use most and perceive as most useful for SRL. The study used a cross-sectional survey design with 120 technology education undergraduate pre-service teachers. A questionnaire was distributed during the Technology Education period and collected after 45 minutes. Principal Component Analysis (PCA) determined the most BLB applications and their perceived usefulness, while a t-test examined male and female differences in the use and usefulness of BLB applications for SRL. Both tests were done using SPSS version 22. The major result shows half of all BLB applications perceived as useful were the ones used most and had positive associations. Three out of eight accounted for 95.69% of the use, while four applications accounted for 73.33% variances in usefulness. Component loadings 1-3 for BLB use variance were: subject content 80.9%, assessment 11.2%, and 3.55%, while usefulness components 1-4 variance were: subject content 26.7%, assessment 17.9%, class task 16.1%, and grade centre 12.6%. There were differences between gender in the use and usefulness of BLB applications, with males taking the lead in both. Thus, this study extends the debate on the gender gap in technology use in higher education.